2011
DOI: 10.1093/ecam/nep059
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Savda Munziq, an Herbal Preparation of Traditional Uighur Medicine, May Prevent 1,2‐dimethylhydrazine‐Induced Rat Colon Carcinogenesis

Abstract: The study tried to assess the chemoprotective effect of abnormal Savda Munziq (ASMq) on 1,2-dimethylhydrazine (DMH)-induced rat colon carcinogenesis. Male F344 rats were randomized into eight groups: Group 1 was served as control, no DMH injection was given and treated daily with normal saline. Rats in Groups 2–8 were given a single intraperitoneal injection of DMH (20 mg/kg body weight) at the beginning of the study. Group 2 was served as negative control, administered with normal saline until the end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Forst., Euphorbia maculata L., Foeniculum vulgare Mill., Glycyrrhiza glabra L., Lavandula angustifolia Mill., Melissa officinalis L., and Ziziphus jujuba Mill (14). ASMq has been applied to the prevention and treatment of numerous chronic diseases, including cancer, hypertension, diabetes mellitus and memory dysfunction (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forst., Euphorbia maculata L., Foeniculum vulgare Mill., Glycyrrhiza glabra L., Lavandula angustifolia Mill., Melissa officinalis L., and Ziziphus jujuba Mill (14). ASMq has been applied to the prevention and treatment of numerous chronic diseases, including cancer, hypertension, diabetes mellitus and memory dysfunction (15).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ASMq has been shown to modulate cellular and humoral immunity in a combined stress mouse model, protecting mitochondria and DNA against damage induced by OH in a cell-free system (17,22). Furthermore, ASMq is able to inhibit cancer cell proliferation and viability in vitro (15,23,24), and has exhibited anti-tumor properties in vitro (15,(22)(23)(24) and in rats (25). However, its potential protective effects against toxicity induced by doxorubicin and 5-FU have not been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that the traditional Uygur medicine abnormal Savda Munziq, which is heading toward a modernized formula, showed good resistance to oxidation (Kizaibek et al, 2012) and had protective effects against oxidative DNA damage (Yusup et al, 2011). Experiments showed that the abnormal Savda Munziq not only had protective effects on the lipid peroxidation damage caused by free radicals, but also improved mitochondrial sodium oxide dismutase (SOD) and Ca 2+ -Mg 2+ -ATPase activities, and maintained the structural integrity of the mitochondrial membrane (Yusup et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The Abnormal Savda Munziq (ASMq) is the valid prescription towards the treatment and prevention of various tumors in Uighur medicine, and its effects are significant (Yusup et al, 2005;Upur et al, 2011;Yusup et al, 2011;. Cisplatin and docetaxel are the commonly clinically used drugs in the treatment of gynec; ological malignant tumors, with exact efficacy (Wang et al, 2010;Ke et al, 2012;.…”
Section: Introductionmentioning
confidence: 99%